The effect of underwriter’s reputation and auditor’s reputation on underpricing in medium companies taking an initial public offering on the Indonesia stock exchange - Apsari, P. Lelyta Apti Dhina; Yasa, Gerianta Wirawan; Astika, Ida Bagus Putra (International research journal of management, IT and social sciences, 2021)
The purpose of this study is to obtain empirical evidence of the influence of auditor reputation and the effect of underwriter reputation on medium-sized companies that conduct initial public offerings. This research was conducted on 190 companies experiencing underpricing listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period, the research data used in this study is secondary data. The number of samples analyzed was 130 development board companies and experienced underpricing because companies that met the sample criteria. The analytical technique used in this study was Multiple Linear Regression Analysis. The results of the study prove that underwriter reputation has a negative influence on underpricing of medium-sized companies that conduct initial public offerings. The reputation of the auditor has no effect on the underpricing of medium-sized companies that make this initial public offering on the IDX.